Molecular mechanisms and horticultural implications of temperature-induced color variation in Stropharia rugosoannulata mushrooms - Shen Meng; Yan Jing; Wang Ruisen; Quan Xinhua; Yuan Ye; Yao Xiangtan; Jin Qunli (Food Chemistry: Molecular Sciences, 2025)
Cap color is a critical commercial trait in Stropharia rugosoannulata mushrooms, yet the molecular mechanisms underlying its temperature-induced variation remain poorly understood. This study integrated metabolomic and transcriptomic approaches to identify key metabolites and genes associated with the transition of cap color from white to wine-red under different temperature conditions. Metabolomic analysis identified 1913 metabolites, with flavonoid derivatives such as quercetin-3-O-glucoside and kaempferol-based compounds accumulating preferentially in wine-red mushrooms at high temperatures. Transcriptomic analysis revealed 13,428 differentially expressed genes (DEGs), including 36 structural genes in the flavonoid biosynthesis pathway. Notably, upregulation of SrGene13140 (F3′H) and SrGene10248 (F3′5′H) was observed in wine-red mushrooms, suggesting their involvement in red pigment production. In contrast, SrGene10253 (F3′H) was more highly expressed in yellow mushrooms, indicating isoform-specific hydroxylation activity. Integrated gene-metabolite correlation and network analysis highlighted key enzymes, including phenylalanine ammonia lyase (PAL), flavonoid 3′-hydroxylase (F3′H), and 4-coumarate: coenzyme A ligase (4CL), as central regulators of color-related flavonoid biosynthesis. These findings provide valuable insights into the molecular basis of temperature-induced color variation in S. rugosoannulata and offer potential applications in mushroom breeding and horticulture.